2002
DOI: 10.1164/ajrccm.165.6.2106079
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Subcutaneous Infusion of Treprostinil, a Prostacyclin Analogue, in Patients with Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension is a life-threatening disease for which continuous intravenous prostacyclin has proven to be effective. However, this treatment requires a permanent central venous catheter with the associated risk of serious complications such as sepsis, thromboembolism, or syncope. Treprostinil, a stable prostacyclin analogue, can be administered by a continuous subcutaneous infusion, avoiding these risks. We conducted a 12-week, double-blind, placebo-controlled multicenter trial in 470 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
798
5
46

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,290 publications
(868 citation statements)
references
References 21 publications
19
798
5
46
Order By: Relevance
“…Similar results have been obtained with the use of other drugs for pulmonary hypertension, including epoprostenol, 30 beraprost, 31 and treprostinil. 28 Hemodynamic assessments of preinhalation values showed that values stabilized in the iloprost group, whereas they deteriorated in the placebo group. The degree of deterioration may be underestimated, since patients who discontinued treatment prematurely did not undergo follow-up hemodynamic examination.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results have been obtained with the use of other drugs for pulmonary hypertension, including epoprostenol, 30 beraprost, 31 and treprostinil. 28 Hemodynamic assessments of preinhalation values showed that values stabilized in the iloprost group, whereas they deteriorated in the placebo group. The degree of deterioration may be underestimated, since patients who discontinued treatment prematurely did not undergo follow-up hemodynamic examination.…”
Section: Discussionmentioning
confidence: 97%
“…2,28 Thus, targeted delivery of prostanoids to the pulmonary vasculature by means of inhalation may substantially reduce the drug requirements.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term persistence of efficacy has also been shown [79,97] can be accomplished by a microinfusion pump and a small subcutaneous catheter. The effects of treprostinil in PAH were studied in the largest worldwide RCT performed in this condition, and showed improvements in exercise capacity, haemodynamics and symptoms [128]. The greatest exercise improvement was observed in patients who were more compromised at baseline and in subjects who could tolerate the upper quartile dose (.…”
Section: Prostanoidsmentioning
confidence: 99%
“…46 There was statistically significant improvement in median exercise capacity, haemodynamics and clinical events compared to placebo group after 12 weeks of treatment with subcutaneous treprostinil. The effect was dose related.…”
Section: Treprostinilmentioning
confidence: 84%